On the Differences in Precipitation Type Between the Arctic, Antarctica and Tibetan Plateau - Yang, Diyi; Ding, Minghu; Dou, Tingfeng; Han, Wei; Liu, Weigang; Zhang, Jianyong; Du, Zhiheng; Xiao, Cunde (Frontiers in Earth Science, 2021)
Under the global warming effect, more precipitation will shift to rainfall in cryospheric regions. Considering the influence of the precipitation type on surface energy and mass cycles, it is important to determine the specific precipitation features and correctly classify the precipitation type in key areas. Based on daily precipitation and air temperature observations from six tripolar stations, we analyzed the monthly distribution, variations in the annual days and trends of each precipitation type. The results indicated that snow dominated the precipitation type at Zhongshan station (69.4°S, 76.4°E) throughout the year, while the Greatwall station (62.2°S, 59.0°W) exhibited a relatively diverse precipitation type distribution and significant seasonal cycles. Compared to the Greatwall station, every precipitation type was less frequently encountered at the Barrow (71.3°N, 156.8°W), Coral Harbour (64.2°N, 83.4°W), Linzhi (29.6°N, 94.5°E) and Maqu stations (34°N, 102.1°E), in which all the sites demonstrated classical reverse seasonal variation. In regard to the trends of the different precipitation types, a consistent trend across the years was found, except at the Greatwall and Coral Harbour stations. Due to snow/rain conditions partly converting into sleet conditions, which may be related to air temperature changes and synoptic atmospheric activities, inconsistent increasing trends of the sleet days were observed compared to the snow/rain days. In addition, a hyperbolic parameterized model was also fitted to determine the air temperature threshold of precipitation type transitions in this paper. According to the threshold comparison results, a warm bias in the temperature threshold was found at the warm stations, and we also proposed that high relative humidity and low freezing levels were the likely reasons based on the ERA5 reanalysis datasets. Finally, the fitted parameterized model in this paper was proven to perform better than the ERA5 reanalysis datasets through validation. This preliminary research provides observational evidence and possible interpretation of the mechanism of precipitation type changes in tripolar areas.